Temperature and Climate Dynamics in National Capital Region of India - Areesha, Areesha; Chauhan, Pankaj; Ahmed, Rizwan; Bhaduri, Sanjukta; Singh, Dharmaveer; Ali, Md Kaikubad (Faculty of Geography, Universitas Gadjah Mada, 2025)
Climate change and increase in global surface temperature are growing concerns worldwide, especially big urban agglomerations like National Capital Region of India, New Delhi and surrounding region have experienced exponential urbanization paving way to horizontal spilling of urban built-up areas, which consequently amplifid the climate variability and surface temperature change over the past few decades. Threfore, the city is highly susceptible to several climate extremes, including heat waves, cold waves, droughts, and flods, impacting socioeconomic lives of over 20 million population. In this study, we applied remote sensing and GIS approaches to study climate variability and its impacts on urban areas. Indicators such as the Land Surface Temperature (LST), Urban Heat Islands (UHI), Normalized Diffrence Vegetation Index (NDVI), and Land Use Land Cover (LULC), were calculated using satellite data for the years 1993, 2000, 2010, and 2020. Th result shows that LST values sharply rose as the maximum value reached 6.9°C in the last three decades (1993-2020), and UHIs maximum values reached 1.76, indicating a clear warming trend in the study area. During this period, the NDVI levels have decreased considerably, going from 0.59 to 0.21, which can be attributed to the expanding urbanization and the decreased green area. Th LULC loss and gain analysis revealed that the urban area has rapidly expanded. In contrast, it resulted in loss of agricultural land, barren and scrubs, water bodies and forest area. Th results show vast climate variability in the region posing threat to environment and socio-economic livelihood of the population.